Digging for the history of man. part 2 700 A.D. (Northbrook, Ill. Roland Collection of Films in Art, 1987)
Presents an archeological examination of the ruins of Sassanian architecture which marked the finale of ancient Persia.
VHS format.
Music, Enno Dugend.
Keywords: Architecture, Sassanid